Public Awareness and Perception of the Smart City Concept in Kuwait: Evaluating Its Six Key Dimensions - Alzougool, Basil; Banna, Sumayya (Informing science, 2025)
Aim/Purpose This study explored public perceptions of the smart city concept in Kuwait and assessed their understanding of its features and dimensions. Background Over the past decade, the notion of “smart cities” has gained significant traction, with numerous urban areas eager to embrace this digital evolution. For a city to transition into a smart city, it must develop a service strategy that places the public as the primary beneficiary of the smart city services. Methodology The study employed the Smart City Wheel model, encompassing six key dimensions of a smart city: governance, mobility, people, economy, living, and environment. The ‘smartness’ of a city is assessed based on the level of advancement in these six key dimensions. To achieve the study’s objectives, 434 individuals were surveyed quantitatively. Contribution Existing studies highlight growing awareness of smart cities and the impact of visibility and demographics but often lack analysis of public perceptions of specific technologies. This study bridges that gap by examining public awareness and perceptions of Smart Cities in Kuwait. Findings The results revealed that just under half of the participants had some understanding of Smart Cities, reflecting moderate community awareness. More than a third of those aware believe their city is working towards becoming smart. However, over half of the respondents are unaware of the concept, indicating a significant knowledge gap. Among the unaware, more than a quarter think local authorities have made efforts to inform the public. Despite this, over three-quarters are interested in learning about Smart Cities, and two-thirds want to engage in city development decisions through digital platforms, demonstrating a potential for public involvement in smart city initiatives. Respondents strongly associate the six key dimensions with the Smart City concept, ranking their importance as follows: smart governance, smart mobility, smart environment, smart living, smart economy, and smart people. The most frequent activities were observed in smart people, smart economy, and smart living. Improvement needs are diverse, with frequent calls for enhancement in smart environment, smart living, and smart mobility. The results also reveal notable variations in the perceived importance of the dimensions and their correlations with the Smart City concept based on employment status, age, and education. Future Research Future research should explore alternative models and dimensions to provide a more comprehensive understanding of smart cities. To enhance the generalizability of the findings, a larger-scale survey conducted over a more comprehensive geographical range would be beneficial.